Large eddy simulations of a circular orifice jet with and without a cross-sectional exit plate - 张健鹏 徐敏义 米建春 (Chinese physics B, 2014)
The effect of a cross-sectional exit plane on the downstream mixing characteristics of a circular turbulent jet is in- vestigated using large eddy simulation （LES）. The turbulent jet is issued from an orifice-type nozzle at an exit Reynolds number of 5 ×104. Both instantaneous and statistical velocity fields of the jet are provided. Results show that the rates of the mean velocity decay and jet spread are both higher in the case with the exit plate than without it. The existence of the plate is found to increase the downstream entrainment rate by about 10% on average over the axial range of 8-30de （exit diameter）. Also, the presence of the plate enables the formation of vortex rings to occur further downstream by 0.5-1 .Ode. A physical insight into the near-field jet is provided to explain the importance of the boundary conditions in the evolution of a turbulent jet. In addition, a method of using the decay of the centreline velocity and the half-width of the jet to calculate the entrainment rate is proposed.